Analysis of the Comparison of Science Literacy Skills of Students at MTS Nurul Huda Situbondo in Solving PISA Science Problems - Musyarofah, Alivinda Aulia Safira; Anggraini, Azza Liarista; Sudarti, Sudarti; Handayani, Rif’ati Dina; Jamhari, Muhammad; Haeruddin, Haeruddin (LP. Ma'arif Janggan Magetan, 2023)
PISA (Program for International Student Assessment) is an international assessment designed to measure students' literacy abilities in various disciplines, including science. This research aims to analyze the scientific literacy abilities of students at MTS Nurul Huda Situbondo in solving PISA Science questions. The research method used is data analysis from the results of the PISA Science test given to students. The data described includes test results based on problem-solving and reasoning assessment rubrics. The research results show that most students need help solving these questions, such as understanding questions well, misinterpreting images, applying scientific knowledge, and relating them to real life. The results of the analysis also show that there is significant variation in abilities among students. The results of the Kruskal Wallis-H test show a p-value <0.05, which means there is a substantial difference between the 3 dependent variables. Some students demonstrate scientific literacy in analyzing and solving PISA science questions, while others still need further assistance. The research results will provide insight into the challenges in solving PISA Science questions by students and improving science education at MTS Nurul Huda Situbondo. Understanding and overcoming these obstacles can prepare students to compete globally, especially in science.